ANALISIS PENGARUH BEBAN TERHADAP LAJU KEAUSAN ALUMINIUM DENGAN PELUMAS SAE 40 PADA PENGUJIAN PIN ON DISC - Widjaja, Daniel Setia (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Tribometer is a device used to measure friction and wear between two surfaces. One type of tribometer that is often used is the pin on disc tribometer. The pin on disc tribometer test tool consists of pins made of certain materials and plates can also be varied according to testing needs. The disc will rotate and the pin is given a load so that the surface of the pin presses against the surface of the disc. In some tribometers, the pin is conditioned to be stationary, but in other tribometers, the pin moves when a load is applied to cause sliding. With this frictional force, wear and tear will be known and besides that, it is used to determine the performance test of a lubricant. A material is applied to the moving part during the test. The final measurement shows wear and tear on the material and is often used to determine the strength and length of nuts.